Research and technology transfer for livestock development - Ehui, Simeon K.; Shapiro, Barry I. (Food and Agriculture Organization of the United Nations, 1995)
A framework for international action to support livestock development is presented and discussed. The goal is to help achieve increased and sustainable food production and generate revenue for improved food security in low income countries. This goal conforms to the global mandate of ILRI which, although its main function is research, cannot ignore the linking of research to technology transfer if it is to make an impact. Issues related to the role of livestock research in strategies making up the action framework and especially effective linkage with technology transfer are discussed. Africa is the focus, because, although it is not unique in facing the problems of low income countries, it provides the greatest challenge to the global agricultural development community.